Synthesis, steady-state, and femtosecond transient absorption studies of resorcinol bound ruthenium(ii)- and osmium(ii)-polypyridyl complexes on nano-TiO2 surface in water - Banerjee, Tanmay; Kaniyankandy, Sreejith; Das, Amitava; Ghosh, Hirendra Nath (Inorganic Chemistry, 2013)
The synthesis of two new ruthenium(II)- and osmium(II)-polypyridyl complexes 3 and 4, respectively, with resorcinol as the enediol anchoring moiety, is described. Steady-state photochemical and electrochemical studies of the two sensitizer dyes confirm strong binding of the dyes to TiO2 in water. Femtosecond transient absorption studies have been carried out on the dye–TiO2 systems in water to reveal <120 fs and 1.5 ps electron injection times along with 30% slower back electron transfer time for the ruthenium complex 3. However, the corresponding osmium complex 4 shows strikingly different behavior for which only a <120 fs ultrafast injection is observed. Most remarkably, the back electron transfer is faster as compared to the corresponding catechol analogue of the dye. The origin and the consequences of such profound effects on the ultrafast interfacial dynamics are discussed. This Article on the electron transfer dynamics of the aforesaid systems reinforces the possibility of resorcinol being explored and developed as an extremely efficient binding moiety for use in dye-sensitized solar cells.